Learning Environment and Early Childhood Character Development in Bronfenbrenner's Ecological Systems Theory - Sofni Indah Arifa Lubis; Zannatun Nisya; Yuliana Lubis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
An early childhood child is an individual who actively interacts with individuals around them. From these direct interactions, children learn social norms and ethics that shape and develop their character. This study focused on the process of early childhood learning from the environment in developing their character from Bronfenbrenner's Ecological Systems theory framework. Eleven interviewees participated in this qualitative research. The findings revealed that at the mesosytem level, a learning environment in the community that is safe and supportive of children's growth and development will develop children's positive character. These results corroborated that positive interactions within the environmental layers in Bronfenbrenner's Ecological Systems Theory will contribute positively to children's development. Parents and RuPin Coordinators unanimously stated that education contributes positively to children's growth and development. Even the smallest knowledge gained by children will affect their mindset and behavior, so a commitment to providing a safe and positively stimulating learning environment is important. From the perspective of Bronfenbrenner's ecological systems theory, an adequate learning environment for young children should involve positive interactions between various environmental systems: family, school, peers and community.